Heat transfer due to impinging co-axial jets and the jets' fluid flow characteristics - Celik, Nevin; Eren, Haydar (Elsevier Science Inc, 2009)
This investigation had multiple goals. One goal was to obtain definitive information about the heat transfer characteristics of co-axial impinging jets, and this was achieved by measurements of the stagnation-point, surface-distribution and average heat transfer coefficients. These results are parameterized by the Reynolds number Re which ranged from 5000 to 25,000, the dimensionless separation distance between the jet exit and the impingement plate HID (4-12), and the ratio of the inner diameters of the inner and outer pipes d/D (0-0.55). The d/D = 0 case corresponds to a single circular jet. The other major goal of this work was to quantify the velocity field of co-axial free jets (impingement plate removed). The velocity-field study included both measurements of the mean velocity and the turbulence intensity. It was found that the variation of the stagnation-point heat transfer coefficient with d/D attained a maximum at d/D = 0.55. Furthermore, the variation of the local heat transfer coefficient across the impingement surface was more peaked for d/D = 0 and became flatter with decreasing d/D. This suggests that for cooling a broad expanse of surface, co-axial jets of high d/D are preferable. On the other hand, for localized cooling, the single jet (d/D = 0) performed the best. In general, for a given Reynolds number, a co-axial jet yields higher heat transfer coefficients than a single jet. Off-axis velocity peaks were encountered for the jets with d/D = 0.105. The measurements of turbulence intensity yielded values as high as 18%. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Co-axial jet; Impingement heat transfer; Flow dynamics of jets; Turbulence intensity